PEMBAHARUAN HUKUM AGRARIA DI INDONESIA - Suwardi .; Arief Dwi Atmoko (Fakultas Hukum Universitas Narotama, 2019)
The policy of implementing Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA) is centered on services for the people, especially the peasantry, which is the largest part of the Indonesian people whose economic conditions are weak. At that time, the provisions of landreform began to be implemented concerning restrictions on the control of agricultural land, the prohibition of land ownership in a hurry (absentee), redistribution of land affected by landreform and absentee provisions, profit-sharing arrangements and agricultural land pawn. In addition, the abolition of colonial rights and the provisions on the conversion of land rights which were originally stipulated in the old legal instruments, became new rights according to the LoGA